Acute myocardial ischemia: changes of free circulating mtDNA level in blood after occlusion of the upper one-third left descending branch of the coronary artery - N. P. Sudakov; T. P. Popkova; A. I. Katyshev; O. A. Goldberg; M. A. Novikova; S. B. Nikiforov; B. G. Pushkarev; I. V. Klimenkov; S. A. Lepekhova; K. A. Apartsin; S. D. Ezhikeeva; M. N. Ten; et al. (Acta Biomedica Scientifica)
The aim of the present study is to analyze the dynamics of free circulating mtDNA level in blood after occlusion of the upper one-third left descending branch of the coronary artery. We showed that the concentration of free circulating mtDNA of blood tends to decrease 24 hours after ligation; it increased and reached values close to control samples 48 and 72 hours after ligation. These data define the need in further investigation of the dynamics of this parameter during later periods of myocardial infarction modeling that will contribute to objective evaluation of its significance for acute myocardial damage diagnostics and prognosis.